2008
DOI: 10.1007/s11270-008-9938-y
|View full text |Cite
|
Sign up to set email alerts
|

Diazinon Accumulation and Dissipation in Oryza sativa L. Following Simulated Agricultural Runoff Amendment in Flooded Rice Paddies

Abstract: Flooded post-harvest rice paddies were examined as systems for reducing diazinon (organophosphate insecticide) concentrations in stormwater runoff. Two paddies were cultivated in Oryza sativa L. and amended with a 3-h simulated stormwater diazinon runoff event. Initial diazinon adsorption peaked at 347 and 571 μg kg −1 (3% mass load reduction) for mean above-ground plant tissue concentrations in each pond, respectively. Subsequent senescence of above-ground tissue showed significant decreases in tissue mass (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…This result was similar to the 1 to 3% diazinon mass measured in rice plants in a larger study area (0.3 ha) reported by Moore et al (2009). Kröger et al (2009) reported that at peak sorption, only 3% diazinon mass load was associated with aboveground plant tissue. In a constructed wetland in the Mississippi Delta, Moore et al (2007) reported 43, 23, and 34% of measured diazinon mass was associated with plants, sediment, and water, respectively.…”
Section: Resultssupporting
confidence: 90%
“…This result was similar to the 1 to 3% diazinon mass measured in rice plants in a larger study area (0.3 ha) reported by Moore et al (2009). Kröger et al (2009) reported that at peak sorption, only 3% diazinon mass load was associated with aboveground plant tissue. In a constructed wetland in the Mississippi Delta, Moore et al (2007) reported 43, 23, and 34% of measured diazinon mass was associated with plants, sediment, and water, respectively.…”
Section: Resultssupporting
confidence: 90%